Resettlement challenges faced by refugee claimant families in Montreal: lack of access to child care. Issue 3 (30th March 2012) - Morantz, Gillian; Rousseau, Cécile; Banerji, Anna; Martin, Carolina; Heymann, Jody
ABSTRACT Adult refugee claimants experience several well‐documented post‐migratory challenges. Little is known about the resettlement process for refugee claimant families with children. This study reports on 75 open‐ended, in‐depth interviews with refugee claimant families in Montreal about their resettlement challenges and their proposed solutions to them. These interviews were conducted with 33 dyads and triads of children and parents attending a paediatric hospital. Experiences accessing formal and informal child care in Montreal were addressed. Subsequently, a comparative policy analysis was conducted on residency eligibility criteria for child care subsidization. Twenty‐eight out of 39 parents (73%) report a lack of informal or formal child care and 15 out of 33 families (39%) propose improving access to formal child care services. They describe a lack of informal child care as a result of reduced social networks, and affordability as a barrier to formal child care services. Refugee claimants are not eligible for subsidized child care in Quebec. A comparative policy analysis within Canada and comparable countries reveals that this situation is not unique to Quebec. However, most provinces and European countries offer child care subsidies to refugee claimants. Refugee claimants should qualify for child care subsidies. Social workers and community organizations should consider their clients' child care needs in designing programmes and services.